Succession of soil-living Nematoda and Diptera larvae (Chironomidae, Sciaridae, and Brachycera) near a melting glacier in Southern Norway - Christer Magnusson; Endre Willassen; Sigmund Hågvar (Arctic, Antarctic, and Alpine Research)
Diptera larvae and Nematoda were extracted from soil samples collected in the foreland of the receding Hardangerjøkulen glacier near Finse, central south Norway. Samples were standardized by being taken in snowbed habitats with Salix herbacea L. vegetation. Diptera larvae were sampled in twenty plots from 32 to 227 years age, complemented by five plots with about 10,000-year-old soil. Nematodes were studied in soils of 4, 37, 39, 62, 78, 119, and 204 years age. There was a rapid colonization in young soils of both Diptera larvae and nematodes. Brachycera larvae were sparsely represented, and Sciaridae and Chironomidae larvae were most numerous in soils younger than 50 years. Genera of Chironomidae larvae were Bryophaenocladius, Pseudosmittia, Parasmittia, and Smittia. The number of nematode taxa increased from six in the youngest soil to fourteen in the oldest. Bacterial feeders were dominated by the genus Rhabditis sensu lato and fungal feeders by Tylenchus sensu lato. The plant-parasitic Paratylenchus sp. was present at 4 years, with highest abundance at 39 years. The abundance of omnivores (subfamily Dorylaiminae) did not vary between soil ages, but predators (fam. Mononchidae and genus Tripyla) were more abundant at 78 and 119 years.